Clinical features, laboratory and molecular findings of children with leukocyte adhesion deficiency type-III from a single center in India - Akshaya Chougule; Prasad Taur; Vaishnavi V. Iyengar; Vijaya Gowri; Bipin P. Kulkarni; Manisha R. Madkaikar; Minnie Bodhanwala; Mukesh M. Desai (Elsevier, 2023)
Leukocyte adhesion deficiency (LAD) Type-III is caused by homozygous mutations in FERMT3 causing Kindlin-3 deficiency. Here we describe three children with molecularly proven LAD-III presenting with neonatal onset mucocutaneous bleeding, infections and persistent neutrophilic leukocytosis. CD18 and CD11a expression on neutrophils was normal in all three, thus ruling out LAD-I. All three had normal platelet glycoprotein expression. Platelet aggregation studies in P2 showed an abnormality similar to Glanzmann thrombasthenia. This article aims to highlight clinical and laboratory clues to the diagnosis of LAD-III, aiding prompt administration of prophylaxis and curative therapy of haematopoietic stem cell transplant.